Penerapan Konseling Spiritual dalam Meredukasi Perilaku Seksual Penyuka Sesama Jenis di Rumah Tahanan - Putra, M.Hafiz Yuza; Suryati, Suryati; Kholili, Ma'rifatin Indah (Journal of Society Counseling, 2024)
This research is about the Application of Spiritual Counseling in Reducing the Sexual Behavior of Homosexuals, and the background to same-sex behavior among inmates, this condition allows the inmates to have contact with fellow residents in the cells. Just one of the inmates who experiences deviant sexual behavior will have an impact on many of the inmates there, this is of course very difficult to find out, especially since physical touch between men is still considered normal. Researchers try to apply spiritual counseling to reach a level of awareness in the inmates so that self-defense by thinking that deviant behavior which they consider to be correct is a wrong action. The research aims to understand the description and the application of spiritual counseling in reducing the sexual behavior of same-sex lovers in the Class 1 Detention Center (RUTAN) in Palembang. The research method used is qualitative. The research subjects were 3 clients FD, FR, and ZE. Data collection techniques through observation, interviews, and documentation. The results of the research show: First, a picture of same-sex sexual behavior can be seen in several prisoners who show an attitude of paying more attention to fellow prisoners in the detention center, then dirty thoughts begin to emerge that want to act more towards people in detention, then the appearance of the prisoner's attitude of wanting a response. the same for the relationship he wants. Second, the diagnosis stage: is identifying the factors that cause same-sex acts in detention centers. Prognosis stage: spiritual guidance and counseling efforts aim to help individuals realize themselves as complete humans to achieve happiness in this world and the hereafter. Therapy stage: encouraging and accompanying clients in studying and practicing religious teachings, so that gradually individuals can guide themselves. Evaluation stage: every Friday, recitation activities are held in the detention center prayer room as a follow-up to the counseling process which indirectly organizes activities for prisoners to participate in congregational prayers and praying for forgiveness from Allah SWT.